The Conception of Patuntung as the Root of Tradition in the Education of the Ammatoa Kajang Indigenous Community - Afriandi; Bahaking Rama; Siti Syamsudduha; Susmihara (Lembaga Bale Literasi, 2026)
This manuscript serves as a template to assist authors in writing the Globalization and modernization have reshaped the value systems and educational practices of indigenous communities, including the Ammatoa Kajang community in South Sulawesi, Indonesia. In this context, education is not merely a formal process but a culturally embedded practice rooted in indigenous belief systems. This study aims to analyze Patuntung-based education as a foundation of indigenous learning, focusing on its epistemological, pedagogical, and axiological dimensions, as well as its role in responding to social change. This research employed a qualitative ethnographic approach, using participant observation, in-depth interviews, and document analysis, analyzed through an interactive model. The findings reveal that Patuntung functions as an indigenous educational framework that structures knowledge construction, value internalization, and social behavior. Its values are transmitted through Pasang ri Kajang in a cyclical process of cultural reproduction. Furthermore, the study identifies a hybrid educational system in which traditional and formal education coexist without eroding cultural identity. This study contributes to the anthropology of education by proposing Patuntung-based education as a conceptual model of indigenous learning that is holistic, adaptive, and sustainable.